2009
DOI: 10.1073/pnas.0905497106
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of adaptation on correlated fitness landscapes

Abstract: Evolutionary theory predicts that a population in a new environment will accumulate adaptive substitutions, but precisely how they accumulate is poorly understood. The dynamics of adaptation depend on the underlying fitness landscape. Virtually nothing is known about fitness landscapes in nature, and few methods allow us to infer the landscape from empirical data. With a view toward this inference problem, we have developed a theory that, in the weak-mutation limit, predicts how a population's mean fitness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(206 citation statements)
references
References 57 publications
(100 reference statements)
11
189
0
Order By: Relevance
“…One of the most successful characterizations of a fitness landscape is to assume a distribution of mutational effects. In this theoretical approach, mutations cause organisms to climb up or down a ladder of fitnesses (49)(50)(51), and the resulting models can result in many cooccurring types (52). It has recently been shown that this "clonal interference" regime generates bursts of branching on coarsegrained scales (53), with fitter lineages expanding quickly toward fixation before being overtaken by yet fitter lineages.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most successful characterizations of a fitness landscape is to assume a distribution of mutational effects. In this theoretical approach, mutations cause organisms to climb up or down a ladder of fitnesses (49)(50)(51), and the resulting models can result in many cooccurring types (52). It has recently been shown that this "clonal interference" regime generates bursts of branching on coarsegrained scales (53), with fitter lineages expanding quickly toward fixation before being overtaken by yet fitter lineages.…”
Section: Discussionmentioning
confidence: 99%
“…This trend can explain the general tendency for the rate of adaptation to decline in populations that are selected in constant environments [16]. However, that work considered genetic backgrounds that differed by only a few mutations and it is not clear if the same pattern will be seen between mutations in divergent backgrounds.…”
Section: (B) Epistasis Depends On Genetic Backgroundmentioning
confidence: 97%
“…For example, several studies have examined specific examples of epistasis causing evolutionary contingency [12,13]. Other studies have demonstrated a trend for beneficial mutations to interact antagonistically, causing the rate of adaptation to slow as beneficial mutations accumulate [8,9,15], a relationship predicted by theory [16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies reveal complex dynamics, characterized by rapid adaptation, competition between beneficial mutations, diminishing-returns epistasis, and extensive genetic parallelism. These forces alter patterns of polymorphism 11 and influence which mutations ultimately fix 1215 . However, it is unclear whether these dynamics are general or, instead, reflect the short timescales and novel environmental conditions of previous studies.…”
mentioning
confidence: 99%